PENGARUH FITUR LAYANAN, KEMUDAHAN, DAN KEAMANAN TERHADAP KEPUASAN PENGGUNA E-WALLET DANA DALAM PERSPEKTIF EKONOMI ISLAM - Sadiah, Mahmudah; Ahmad Su`aib (I'THISOM : Jurnal Ekonomi Syariah, 2025)
This research aims to determine the influence of service features, convenience and security on DANA e-wallet user satisfaction. This type of research is quantitative research using the Jepara population who use the DANA e-wallet. Sampling was based on non-probability sampling with a purposive sampling method. Data collection was obtained from a questionnaire which was measured using a Likert scale and data processing was carried out by SPSS version 26 using the multiple linear regression analysis method. The validity of the data is based on validity and reliability tests and then analyzed using the classic assumption test. The research results explain that partially the service and security feature variables have a positive but not significant effect. The difference in the convenience variable produces a positive and significant influence on DANA e-wallet user satisfaction.